Front Cover: Long‐Term Generation of Longitudinal Spin Order Controlled by Ammonia Ligation Enables Rapid SABRE Hyperpolarized 2D NMR (12/2021). Issue 12 (17th June 2021) - Vaneeckhaute, Ewoud; De Ridder, Sophie; Tyburn, Jean‐Max; Kempf, James G.; Taulelle, Francis; Martens, Johan A.; Breynaert, Eric
Abstract : The Front Cover The image shows the reciprocity between parahydrogen, deuterated ammonia and iridium allowing for hyperpolarized 2D NMR via long‐term availability of longitudinal spin order. More information can be found in the Article by Eric Breynaert and co‐workers .